A quantitative real time polymerase chain reaction approach for estimating processed animal proteins in feed: preliminary data - Maria Cesarina Abete; Beatrice Brusa; Stefania Squadrone; Alessandro Benedetto; Giuseppina Amato; Daniela Marchis (Italian Journal of Food Safety, 2013)
Lifting of the ban on the use of processed animal proteins (PAPs) from non-ruminants in non-ruminant feed is in the wind, avoiding intraspecies recycling. Discrimination of species will be performed through polymerase chain reaction (PCR), which is at a moment a merely qualitative method. Nevertheless, quantification of PAPs in feed is needed. The aim of this study was to approach the quantitative determination of PAPs in feed through Real Time (RT)-PCR technique; three different protocols picked up from the literature were tested. Three different kind of matrices were examined: pure animal meals (bovine, chicken and pork); one feed sample certified by the European reference laboratory on animal proteins (EURL AP) in feed spiked with 0.1% bovine meal; and genomic DNAs from bovine, chicken and pork muscles. The limit of detection (LOD) of the three protocols was set up. All the results obtained from the three protocols considered failed in the quantification process, most likely due to the uncertain copy numbers of the analytical targets chosen. This preliminary study will allow us to address further investigations, with the purpose of developing a RT-PCR quantitative method.